2018
DOI: 10.1098/rsos.171875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar on the fate and toxicity of herbicide fenoxaprop-ethyl in soil

Abstract: Biochar, as a soil amendment in agriculture, has attracted considerable attention. In the study, the fate and toxicity of the herbicide fenoxaprop-ethyl were evaluated in soils with and without 5% rice husk biochar amendment. Fenoxaprop-ethyl and metabolite fenoxaprop degradation followed first-order kinetics in the two soils. Fenoxaprop-ethyl decreased fast with half-lives less than 2 days. Large amounts of fenoxaprop formed and remained in the control soil. However, fenoxaprop was much lower in the biochar-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Biochar has been shown to improve survival rates in the manner reported in our study. Jing et al [35] observed no earthworm death in 5% biochar-amended soil after 28 days of exposure of E. fetida to fenoxaprop-ethyl. Nyoka et al [20] found that E. fetida exposed to imidacloprid in 10% biochar-amended soils experienced significant improvement in survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar has been shown to improve survival rates in the manner reported in our study. Jing et al [35] observed no earthworm death in 5% biochar-amended soil after 28 days of exposure of E. fetida to fenoxaprop-ethyl. Nyoka et al [20] found that E. fetida exposed to imidacloprid in 10% biochar-amended soils experienced significant improvement in survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…The growth curve of Bacillus cereus strain JCM 2152 suggested that PKS biochar is a suitable carrier material which provides favourable environment for the proliferation and immobilization of the bacteria due to its high porosity, pore volume and non-toxic nature. It also acts as the carbon and nutrient sources such as N, P and K to the immobilized cells [36]. This occurrence was attributed to high diffusion concentration gradient at initial phase, which increased the rate of diffusion (driving force) and hence mass transport of bacteria to biochar [37].…”
Section: Adsorption Of Bacillus Strains Onto Biocharmentioning
confidence: 99%
“…The degradation of FEN was relatively slow in water with half-lives of 6.4-12.4 days (Jing et al 2016),and the half-lives of FEN in soil was 56.9 days (Jing et al 2018). Therefore, FEN exhibited potential risk to the aquatic animals after using in rice eld.…”
Section: Introductionmentioning
confidence: 99%